Articulating the Shape: transversal pedagogical actions for the construction of the visual syntax knowledge (ModaPalavra e-periódico, 2020)
The article emphasizes the development of the ability toarticulate visual / formal syntax as a fundamental way forthe consolidation of project thinking among fashion designstudents.From exploratory approach, integrates tworesearch focus: the first studies the self-regulation oflearning in project teaching; the second one addressesmethodological strategies for the development of the abilitycompositional synthesis. Thus, the study examines practicesfor Visual Methodology learning at the Bachelor of theFashion Design at State University of Londrina, searchingeffectivecontributionstheexperimentalcreativemanipulation and decomposition of visual messages.To thatoccurs, a combined pedagogical action is analyzed, aiming atthe proof of its didacticscholarship. The results confirm thepotential of action and self-regulated learning strategies asfacilitators of the ability to generate expressive andconfigurable concepts of artifacts in the field of fashion
Keywords: fashion design; visual syntax; project